Evaluasi Sistem Manajemen Keselamatan Dan Kesehatan Kerja (SMK3) Di Perusahaan Industri Baja - Fitria Ciptaningsih; - Ekawati; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
K3 is an activitiy to ensure and protect the safety and health of workers through prevention of occupational accidents and occupational diseases. One of prevention accident method is by SMK3. SMK3 process should begin with good planning so that the application is fits with the policies and objectives expected. Steel company industry has already applied SMK3 which arranged in company management system, but in implementation SMK3 was not applied fully yet. The purpose of this study is to evaluate the application of planning K3 in steel company industry. This study uses qualitative research with observational approach. Informants in this study were employees of company who involved in planning K3. Instrument in this study were manual of interview and observation sheet. Based on the result of indepth interviews and observations, it showed that SMK3 implementation in company not fit fully yet with PP RI nomor 50 tahun 2012, there were some things that have not been completed, which are training and competence planning for employees , explanation of the responsibility and authority for employees level, and procedure of the responsibility changes